Sustainable Livelihood Strategies of Riverine Communities at Sadong Jaya, Sarawak - Su Jin, Tan (2023)
This study uses the sustainable livelihood approach to examine the livelihood assets and livelihood strategies adopted by the riverine communities at Sadong Jaya, Sarawak as well as the vulnerabilities faced by them. A mixed method approach was adopted in this study. Data was collected from focus group discussions, observations, and face-to-face interviews with 243 households in which the samples were drawn from three clusters (upper estuarine, middle estuarine and lower estuarine) in Sadong Jaya using a multi-stage sampling method. The study found that, due to the dynamic nature of the local environment with its unique geographical location prone to flash flood and monsoon flood besides environment degradation and poor socio-economic conditions, the community is susceptible to a high level of vulnerability. Local people perceived their livelihood vulnerability as the result of poor access to natural resources and limited natural resources to market and basic social amenities such as facing insufficient treated water supply for both household daily consumption besides lacking water for agriculture. The middle estuarine communities are found to be more vulnerable than the upper and lower estuarine communities at Sadong Jaya with the vulnerability index at 0.414 as compared to vulnerability index of 0.394 and 0.410 in upper and lower estuarine respectively. The riverine communities at Sadong Jaya utilize diversified livelihood strategies by optimizing the use of capital assets available to sustain their livelihoods. Communities who are better equipped with an enhanced and diversified assets base are more resilient. Overall, social asset is found to be the most equipped asset in Sadong Jaya while financial asset is the least equipped asset followed by human asset. The study found that infrastructures such as roads and bridges, water supply facilities, drainage systems, watergates and education facilities enable the riverine communities to intensify and diversify economic activities, widen job opportunities, and market opportunities. As accessibility to education and training facilities is made available to the locals through better connectivity facilitated by various physical infrastructure, more riverine communities are involved in non-agricultural economic activities and out-migration to cities and abroad is common in the study area. The regression scores showed that riverine communities in Sadong Jaya are most likely to adopt non-agricultural livelihood activities given that they have higher education and skills level, more purchasing power to own farm tools, better health, better ability to secure financial facilities and sustain disaster conflict and possess more diversification capabilities.